Bioactivity of Vernonia arborea Leaves from Bentian Tribe as Natural Antioxidant and Antibacterial Based on Local Knowledge - Sari, Nur Maulida; Aziza, Humairo; Aryani, Farida; Murdianto, Murdianto (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
The utilization of natural organic materials as raw materials for standardized medicine, including the use of organic materials in medicine manufacture are currently being encouraged by the Government. Based on the information from Bentian Tribe people, Vernonia arborea leaf or Kutu Buâ€™ut leaf has the potential to be developed as natural medicine derived from plants. This study explored the potential of V.arborea leaf for its phytochemicals screening by Harborne, Kokate and Senthilmurugan method, antioxidant analysis was evaluated by DPPH radical scavenging assay. Antibacterial analysis was examined using agar well diffusion method against Escherichia coli and Propionibacterium acnes. The results showed that the V.arborea leaf contained alkaloid on n-hexan extract and coumarin on ethyl acetate extract. Ethanol extract from V.arborea leaf contained alkaloid, flavonoid, saponin, tannin, and carbohydrate. Antioxidant activity showed that the highest inhibition by 83% at 50 ppm consentration of ethanol solvent. Antibacterial activity of E. coli and P.acnes showed that the highest inhibition zone by 12 mm and 11 mm at 400 Âµg/well of ethanol extract. Based on the results, the V.arborea leaf contains natural bioactivity and has potential to be further developed as a natural traditional medicine.